MOLECULAR CHARACTERIZATION OF RYNAXYPYR RESISTANT PLUTELLA XYLOSTELLA (L.) - N. N. PATEL; K. N. PATEL; VINA SAGANE (The Bioscan, 2014)
Present investigation was undertaken to know the biochemical and molecular mechanism of rynaxypyr resistance in Diamondback moth (P. xylostella.) Selection of DBM against rynaxypyr upto seven generations resulted in development of about 34.88 folds resistance. Biochemical studies revealed increased Glutathione-s-transferase and Carboxylesterase activity by 2.385 and 1.57 folds respectively, in resistant strain as compared to susceptible strain. Native PAGE demonstrated the induced and over expression of the respective enzymes. In RAPD-PCR out of 20 primers two primers gave maximum polymorphism and found to be potential markers for rynaxypyr resistance in DBM.